CLINICAL FEATURES AND ASSOCIATED FACTORS OF ACNE VULGARIS PATIENTS AT VIET TIEP FRIENDSHIP HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical characteristics and evaluate several related factors in acne patients.Subjects and Methods: A cross-sectional, descriptive study was conducted on 106 patients who presented for examination and were diagnosed with acne at the Department of Dermatology, Viet Tiep Friendship Hospital, from January 1, 2025, to September 30, 2025. Results: The prevalence was higher in females (56.7%) than in males (43.3%). The mean patient age was 20.9 ± 6.6 years, with patients over 20 years old accounting for a higher proportion (71.7%) compared to those ≤ 20 years old (28.3%). Combination skin was the most common skin type (38.6%), followed by oily skin (27.4%), normal skin (17.9%), dry skin (11.4%), and sensitive skin (4.7%). The most prevalent lesion type was papules (87.7%), followed by pustules (50.9%), comedones (46.2%), and nodules/cysts (2.8%). According to the GAGS (Global Acne Grading System) classification, the most frequently involved areas were Zone I (69.8%), Zone III (59.4%), Zone 4 (53.7%), Zone 5 (51.8%), Zone II (51.4%), and Zone VI (29.3%). Moderate acne was the most common severity (63.2%), followed by mild (18.9%), with severe acne being the least prevalent (17.9%). Age over 20 years (OR = 1.73; CI = 0.60 – 5.01) and all three studied habits showed a trend towards increasing the risk of severe disease: habit of staying up late (OR = 1.36; CI = 0.28 – 6.64); habit of eating sweets (OR = 1.59; CI = 0.42 – 6.02); and habit of squeezing acne lesions (OR = 2.06; CI = 0.43 – 9.08). However, these associations were not statistically significant (p > 0.05). Conclusion: The most common clinical manifestations were papules and pustules. The majority of acne patients had moderate disease severity.
Keywords: Acne, acne vulgaris, symptoms, lesion severity, GAGS, related factors.